Emergency abdominal aortic aneurysm presenting without haemodynamic shock is associated with misdiagnosis and delay in appropriate clinical management. Issue 5 (22nd April 2009) - Gaughan, M; McIntosh, D; Brown, A; Laws, D
Abstract : Background: Emergency abdominal aortic aneurysm (EmAAA) represents a spectrum of disease from symptomatic non-ruptured aneurysms to free intraperitoneal rupture, with significantly worse outcomes for patients in a haemodynamically shocked state before surgery. A study was undertaken to see if the preoperative journey and outcome were different in patients who deviated from the classic acutely shocked presentation. Methods: An observational database compiled from case notes of patients undergoing surgery for EmAAA at Sunderland Royal Hospital between April 2000 and October 2006 was interrogated to examine details of patient preoperative journey, physiological status and 30-day survival. Comparison between groups was performed using χ 2 analysis and the Mann-Whitney U test where appropriate. Results: Records for 98 patients were available for review. Overall 30-day mortality was 49%, and was significantly higher for patients in shock at induction of anaesthesia than in those who were haemodynamically stable (59.6% vs 34.1%, p = 0.01). At presentation, 56 patients were stable and misdiagnosis was significantly more common in these patients than in those who were in shock (58.9% vs 26.2%, p = 0.002), with a significantly increased median time delay from presentation to diagnosis (144 min (IQR 24–366) vs 12 min (IQR 0–42), p<0.0001). Median time from diagnosis to arrival in theatre was significantly longer in patients who were haemodynamically stable at presentation (90 min (IQR 60–150) vs 48 min (IQR 36–90), p = 0.02). Of the 56 patients who were haemodynamically stable at presentation, 19 underwent haemodynamic decompensation before surgery with a significantly increased mortality compared with those who remained stable (73.7% vs 37.8%, p = 0.02). Of these 19 patients, only 5 were correctly diagnosed at presentation. Conclusions: Diagnosis and treatment of EmAAA in haemodynamically stable patients is often delayed, with the risk of significant rupture and haemodynamic decompensation which is associated with poor outcome. Correct diagnosis and treatment before development of shock has the potential to reduce mortality.